2007
DOI: 10.1111/j.1365-2672.2007.03544.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Gram-positive n-alkane degraders from a hydrocarbon-contaminated Mediterranean shoreline

Abstract: Aims:  To investigate the petroleum hydrocarbon (HC)‐degrading potential of indigenous micro‐organisms in a sandy Mediterranean coast, accidentally contaminated with petroleum‐derived HCs. Methods and Results:  Using culturable methods, a population of Gram‐positive n‐alkane degraders was detected in the contaminated soil. Five isolates, identified as one Nocardia, two Rhodococcus and two Gordonia strains, were able to degrade medium‐ and long‐chain n‐alkanes up to C36 as assessed by growth assays and gas chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 40 publications
6
101
0
Order By: Relevance
“…Although some studies have shown that, oil polluted soils are dominated by Gram-negative bacteria (Macnaughton et al, 1999;Kaplan and Kitts, 2004), the dominant culturable hydrocarbon-utilizing bacteria from the soil investigated were made up of Grampositive Actinobacteria of the genera Pseudomonas, Bacillus, Acinetobacter, Micrococcus and Corynebacterium , this corroborates the findings of Quatrini et al, (2008) who isolated 2 Rhodococcus, 2 Gordonia and 1 Norcadia strains as dominant hydrocarbon-degraders from a hydrocarbon contaminated Mediterranean shoreline.…”
Section: Discussionsupporting
confidence: 77%
“…Although some studies have shown that, oil polluted soils are dominated by Gram-negative bacteria (Macnaughton et al, 1999;Kaplan and Kitts, 2004), the dominant culturable hydrocarbon-utilizing bacteria from the soil investigated were made up of Grampositive Actinobacteria of the genera Pseudomonas, Bacillus, Acinetobacter, Micrococcus and Corynebacterium , this corroborates the findings of Quatrini et al, (2008) who isolated 2 Rhodococcus, 2 Gordonia and 1 Norcadia strains as dominant hydrocarbon-degraders from a hydrocarbon contaminated Mediterranean shoreline.…”
Section: Discussionsupporting
confidence: 77%
“…Many microbial isolates in these genera were recognized as oil-degrading microorganisms by earlier researchers, such as Muthukumar et al (2003), Chaerun et al (2004), Al-Awadhi et al (2007) and Quatrini et al (2008). The presence of various crude oildegrading microorganisms corresponded to the contamination of petroleum hydrocarbons in Thai coastal areas (Wattayakorn, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Ud-4 isolated from seawater degraded 32% of 1% lubricant during the same period (Tanaka et al, 2010). Bacteria in the genus Gordonia have been isolated from various petroleum hydrocarbon-contaminated sites, including oily seawater (Arenskötter et al, 2004;Brito et al, 2006;Quatrini et al, 2008;Shen et al, 2008). Earlier reports demonstrated that Gordonia persist in severe conditions and possess special cellular physiology, including high cell surface hydrophobicity, emulsifi cation activity and EPS synthesis, to enhance hydrophobic substrate uptake (Arenskötter et al, 2004;Franzetti et al, 2009;Fusconi et al, 2006Fusconi et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…However, the bacterial diversity of tropical ecosystems is less explored. In bioremediation, the detoxification of organic contaminants has been established as an efficient, economic, versatile and environmentally sound treatment (Margesin et al 2003;Nweke and Okpokwasili 2004;Kaplan and Kitts 2004;Quatrini et al 2008). This is possible because the microorganisms have catabolic gene pool that is necessary for synthesizing the enzymes that can mediate the critical steps in diesel oil degradation.…”
Section: Introductionmentioning
confidence: 99%